Judging judges : values and the rule of law - Whitehead, Jason E., 1970- (Baylor University Press, 2014)
The "rule of law" stands at the heart of the American legal system. But the rule of law does not require judges slavishly to follow the letter of the law, unaffected by political or social influences. Because following the rule of law absolutely is impossible, it is dismissed by the public as a myth and judges are vilified. Judging Judges refocuses and elevates the debate over judges and the rule of law by showing that personal and professional values matter. Jason E. Whitehead demonstrates that the rule of law depends on a socially constructed attitude of legal obligation that spawns objective.